Analysis of Politeness Maxims Found in Lady Chatterley’s Lover Movie - Ni Made Sri Maheswari Paramitha; Komang Dian Puspita Candra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
Politeness has always been one of the primary linguistics issues. The objectives of this research were centered on identifying the varieties of politeness maxims utilized by characters in the 2022 adaptation of the film "Lady Chatterley's Lover." The primary focus of this inquiry was to examine the employed politeness maxims exclusively within the dialogues among the characters. The researcher detailed and assessed both the quantity and prevalence of distinct politeness maxims within the film. For analysis, a qualitative approach was employed, drawing on Leech's (1983) theory that delineates six categories of politeness maxims. The data were gathered through observational means from the British romantic movie titled "Lady Chatterley's Lover" released in 2022. The findings of this investigation exhibit the presence of six distinct classes of applied politeness maxims throughout the movie. The study's outcomes reveal a total of 48 instances categorized as follows: 12 instances of tact maxim, 10 instances of generosity maxim, 8 instances of approbation maxim, 5 instances of modesty maxim, 7 instances of agreement maxim, and 6 instances of sympathy maxim. The highest frequency was observed in the tact maxim category, with 12 instances, signifying its predominant utilization among the characters in the movie.